The Impact of Stratospheric Intrusion on Surface Ozone in Urban Areas of the Northeastern Tibetan Plateau - Mingge Li; Yawen Kong; Meng Fan; Chao Yu; Ying Zhang; Jianbin Gu; Jinhua Tao; Liangfu Chen (Atmosphere)
In recent years, high-altitude cities with low emissions in western China have exhibited an upward trend in surface ozone (O3). Based on observations and reanalysis data, this study analyzed the evolutionary characteristics and pollution mechanisms of ozone in Xining and quantified the impact of stratospheric intrusion. The results indicated that an upward trend in summer O3 was observed in Xining. A total of 29 ozone exceedance days were found. Potential exceedance days (>150 and >140 μg/m3) showed substantial increases from 2022 to 2023. Using a stratospheric intrusion to surface (SITS) event identification algorithm, 42 events were found in Xining, with an average duration of 8.4 h. Spring exhibited the highest event frequency (13 events) and longest average duration. SITS events contributed an average of 19.7% to surface ozone, significantly exacerbating local exceedance risks. A typical ozone pollution episode from 25 July to 3 August 2021 was analyzed. The peak O3 reached 170 μg/m3. Elevated temperature, intensified radiation, and unfavorable meteorological conditions synergistically promoted local photochemical ozone production and accumulation. Notably, a SITS event was simultaneously detected, elevating surface ozone by 24%, which confirmed that stratospheric intrusion was the main cause of pollution.